Tingatinga : the popular paintings from Tanzania - Goscinny, Yves; Finnish Project Compound, Dar-es-Salaam; National Assembly, Dodoma; National Museum, Dar-es-Salaam; Natural History Museum, Arusha; Palace Museum, Zanzibar (Dar-es-Salaam : La Petite Galerie Dar-es-Salaam National Museum Dar-es-Salaam, 2004)
Ajaba, Abdallah ; Amonde, Omary ; Aussi, Jaffary ; Berger, Michael ; Bushir Mruta, Salum ; Bushiry, Awazi ; Challi, E.S. ; Charinda, Mohamed ; Chimwanda, Zaburi M. ; Chiwaya, Rajabu ; Chombo, Rashidy ; Emmanueli Stanislaus, Jeremia ; Fussi, Omary Ally ; Gayo, Peter ; Hassani Kamale, Abdelehemani ; Hassani, Jaribuni ; Issa Iddi, Iddi ; Kambili, Noel ; Kamundi, Max ; Kapunda, Michael Maiko ; Kibira, Jaruph ; Kilaka, John ; Kimambo ; Kirknaes, Jesper ; Lewis, Stephen Mseza ; Lilanga, George ; Lilanga, Henrick ; Linda, John ; Lulandala, Job John ; Maida, Suleimani H. ; Malikita, Maurus Michael ; Malindi Mlaponi, Issa ; Mandu Mmatambwe, Adeusi ; Manyanga, Mohamed ; Manyera, Godfrey ; Martin, Peter ; Masoudi, Jabili ; Matola Kantande, Issa ; Matteuci, Aldo ; Mbaruku, Hemed ; Mbwana, Sudi ; Mikidadi, Bush ; Mimus, Jafari ; Mitole, Issa Said ; Muuhidini Chande, Majidu ; Mwidadi Mpata, Agnes ; Saidi Chilamboni, Abdallah ; Saidi, Amuri ; Samweli, Agustino ; Siyaya, John ; Thabiti Hassani, Mchisa ; Tingatinga, Edward Said
Bibliog. p. 163
Korte biog. per kunstenaar p. 114-160
Publication on the occasion of the exhibition 'Tingatinga: the popular paintings from Tanzania' at the Finnish Project Compound in Dar-es-Salaam, 15.06.2004-25.06.2004 and at the National Assembly in Dodoma, 20.09.2004-01.12.2004 and at the National Museum in Dar-es-Salaam, 13.06.2005-20.06.2004 and at the Natural History Museum in Arusha, 30.06.2004-24.09.2004 and at the Palace Museum in Zanzibar, 06.12.2004-17.06.2005
boek